Home schooling: It’s justifications and importance of its application applying it in Saudi Arabia in light of Islamic Educational Principles - Al-Zahrani, Ali Abdullah Ahmed (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the justifications and importance of applying home education in the Kingdom of Saudi Arabia in the light of Islamic pedagogical principles, with an explanation of the most important educational practices of home education in the Kingdom. The study relies on the descriptive survey method. This approach includes collecting data in order to answer the study questions through the method of questionnaires and discussions. This is to reach conclusions or generalizations that help in understanding home education in a contemporary way, to support decision-making in this regard. To achieve the objectives of the study, the researcher prepared a questionnaire, and then made sure of the validity and reliability thereof. The sample of the study consisted of 362 primary school teachers in Jeddah Governorate. The results, according to the participants’ point of view, are as follows: The level of justifications for providing home education, in the light of Islamic pedagogical principles is Medium, this dimension achieved an arithmetic mean of (2.52), the level of the importance of applying home education, in the light of Islamic pedagogical principles is Medium, this dimension achieved an arithmetic mean of (2.51), the level of the positive side of the pedagogical practices of homeschooling is Medium, this dimension achieved an arithmetic mean of (2.56), the level of the negative side of the educational practices of homeschooling is Medium, this dimension achieved an arithmetic mean of (2.48), The researcher also recommended: developing a clear plan for the home education system that includes: defining the system, its objectives, means of implementation, stages of application, continuous development of the home education system, keeping pace with modern technological developments, and taking the benefits from the experiences of other countries.